Spiritual Intelligence as a Theory of Individual Religion: A Case Application - Kwilecki, Susan (The international journal for the psychology of religion, 2000)
This article considers the utility of Emmons's theory of "spiritual intelligence" for the analysis of the religions of individuals. The hypothesis is divided into a proposed description, explanation, and assessment of the consequences of personal faith. The spiritual biography of Gladys Day, a contemporary African American Pentecostal, provides an empirical format for the consideration of each formulation. Accordingly, the "core components" receive high marks for capturing the essential dynamics of spiritual growth. However, the explanation of personal religion as an expression of a universal capacity for transcendence is relatively weak vis-à-vis one that identifies immediate biographical causes. Attentiveness to differences in religious and secular conceptions of health and adaptation would improve Emmons's assessment of the fruits of spiritual intelligence.